Religion is not about God : how spiritual traditions nurture our biological nature and what to expect when they fail - Rue, Loyal D. (Rutgers University Press, 2005)
Annotation Thousands of religious traditions have appeared over the course of human history but only a relative few have survived. Since some speak of a myriad of gods, others speak of only one, and some recognize no gods at all, we can conclude that belief in a supernatural being is not the only thing that holds a faith tradition together. Volumes have been written attempting to prove the existence or non-existence of supernatural being(s). So, if religion is not about God, then what on earth is it about? In this provocative book, Loyal Rue contends that religion, very basically, is about us. Successful religions are narrative (myth) traditions that influence human nature so that we might think, feel, and act in ways that are good for us, both individually and collectively. Through the use of images, symbols, and rituals, religion promotes reproductive fitness and survival through the facilitation of harmonious social relations. Rue builds his argument by first assembling a theory of human nature, drawn from recent developments in cognitive science and evolutionary theory. He shows how cognitive and emotional systems work together and how they are conditioned by cultural influences, including religion. He then surveys the major religious traditions-Judaism, Christianity, Islam, Hinduism, and Buddhism-to show how each one, in its own way, has guided human behavior to advance the twin goals of personal fulfillment and social coherence. As all religions are increasingly faced with a crisis of intellectual plausibility and moral relevance, they are being rendered incapable of shaping behavior in ways that might prevent unsustainable patterns of human population and consumption. Rue warns that when religions outlive their adaptive utility, they become positive threats to human survival. Despite its bold and ambitious goals, this book is hostile to neither the idea of God nor religious life. Written respectfully throughout, Religion Is Not about God will appeal to a broad audience interested in issues of faith and science.
Keywords: Psychology, Religious.; Genetic psychology.; Psychologie religieuse.; Psychologie génétique.; psychology of religion.; RELIGION -- Psychology of Religion.; Genetic psychology; Psychology, Religious; Religionspsychologie; Philosophie; Religion; Genetische psychologie.; Godsdienstpsychologie.